Intracerebral Hemorrhage Incidence, Mortality, and Association With Oral Anticoagulation Use: A Population Study. Issue 5 (9th March 2021) - Fernando, Shannon M.; Qureshi, Danial; Talarico, Robert; Tanuseputro, Peter; Dowlatshahi, Dar; Sood, Manish M.; Smith, Eric E.; Hill, Michael D.; McCredie, Victoria A.; Scales, Damon C.; English, Shane W.; Rochwerg, Bram; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Spontaneous intracerebral hemorrhage (ICH) is a devastating form of stroke associated with significant morbidity and mortality. Recent epidemiological data on incidence, mortality, and association with oral anticoagulation are needed. Methods: Retrospective cohort study of adult patients (≥18 years) with ICH in the entire population of Ontario, Canada (April 1, 2009–March 30, 2019). We captured outcome data using linked health administrative databases. The primary outcome was mortality during hospitalization, as well as at 1 year following ICH. Results: We included 20 738 patients with ICH. Mean (SD) age was 71.3 (15.1) years, and 52.6% of patients were male. Overall incidence of ICH throughout the study period was 19.1/100 000 person-years and did not markedly change over the study period. In-hospital and 1-year mortality were high (32.4% and 45.4%, respectively). Mortality at 2 years was 49.5%. Only 14.5% of patients were discharged home independently. Over the study period, both in-hospital and 1-year mortality reduced by 10.4% (37.5% to 27.1%, P <0.001) and 7.6% (50.0% to 42.4%, P <0.001), respectively. Use of oral anticoagulation was associated with both in-hospital mortality (adjusted odds ratio 1.37 [95% CI, 1.26–1.49]) and 1-year mortality (hazard ratio, 1.18 [95% CI, 1.12–1.25]) following ICH. Conclusions: Both short- and long-term mortality have decreased in the past decade. Most survivors from ICH are likely to be discharged to long-term care. Oral anticoagulation is associated with both short- and long-term mortality following ICH. These findings highlight the devastating nature of ICH, but also identify significant improvement in outcomes over time.